The Role of Academic Involvement in Ensuring the Quality of Accounting Competency Examinations at Muhammadiyah 6 Vocational High School Medan - Bhastary, Manda Dwipayani; Devia Febrina; Robin; Ika Puspa Satriany; Agus Susanto; Mega Sanjaya; Debora Tambunan; Emma Novirsari; Ahmad Fadli; Martin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
This community service activity aims to enhance the quality of the Accounting Vocational Competency Examination (Ujian Kompetensi Keahlian/UKK) at SMK Muhammadiyah 6 Medan through the active involvement of academic professionals as strategic partners. The school faces several challenges, including limited access to qualified external examiners, a lack of integration between the school curriculum and industry standards, and the need to improve the validity of assessment instruments. The program was conducted through several stages: needs assessment, training in competency-based test development, technical assistance during the UKK implementation, and evaluation of exam outcomes. The results indicate that the involvement of academicians not only improved the validity and reliability of the UKK process but also strengthened the linkage between secondary education and higher education institutions. Moving forward, this collaboration is expected to continue through curriculum alignment and teacher competency development.